Modern Educational Building in Late Ottoman Istanbul: Haydarpaşa German School - Çağdaş Çankaya; Aras Kahraman (Prostor, 2025)
In the late Ottoman period, foreign schools played a crucial role in educational modernization and cultural diplomacy. The Haydarpaşa German School, located in Istanbul and established as a branch of the Galata Bourgeois School, exemplifies Ottoman-German interaction in education and colonial architecture. Archival records reveal complex negotiations between the Ottoman administration and the German Embassy, reflecting broader geopolitical and cultural imperialist dynamics. The school follows the city school model, a disciplinary architectural approach emphasizing hierarchy, control, and efficiency, aligning with late 19th-century German pedagogical principles. A comparative analysis of the Galata Bourgeois and Yedikule German Schools shows that all three institutions adhere to the city school typology. Unlike the prevailing Neo-Ottoman or Orientalist styles, these schools adopted a rigid, regimented design, serving as tools of cultural imperialism. Its transformation after World War I and integration into the Turkish education system reflect shifts in foreign educational policies. Recent restoration efforts balance historical preservation with contemporary needs. This study positions the Haydarpaşa German School as both an architectural artifact and a colonial instrument, contributing to discussions on cultural imperialism, modernization, and education in the late Ottoman period.